2015
DOI: 10.1371/journal.pntd.0003750
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Bacterial Febrile Illnesses in Children in Kilosa District, Tanzania

Abstract: IntroductionBacterial etiologies of non-malaria febrile illnesses have significantly become important due to high mortality and morbidity, particularly in children. Despite their importance, there are few reports on the epidemiology of these diseases in Tanzania, and the true burden of such illnesses remains unknown. This study aimed to identify the prevalence of leptospirosis, brucellosis, typhoid fever and urinary tract infections and their rate of co-infections with malaria.MethodsA cross-sectional study wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
80
1
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(93 citation statements)
references
References 50 publications
(54 reference statements)
6
80
1
4
Order By: Relevance
“…Despite this, we noted a not unsurprising belief amongst laboratory technicians and clinicians working in both study health facilities that the FBAT, marketed with separate ‘abortus’ and ‘melitensis’ antigens, can distinguish between infections with these different Brucella species. This misconception is likely to be strengthened by the inconsistent results obtained with the ‘abortus’ and ‘melitensis’ suspensions of FBAT, as illustrated by our work and recently published work from Tanzania [50]. Long and repeated experience [11,18,24,51] shows that the most plausible reasons for these inconsistencies are deficient standardisation of antigen suspensions and poor antigen quality.…”
Section: Discussionmentioning
confidence: 72%
“…Despite this, we noted a not unsurprising belief amongst laboratory technicians and clinicians working in both study health facilities that the FBAT, marketed with separate ‘abortus’ and ‘melitensis’ antigens, can distinguish between infections with these different Brucella species. This misconception is likely to be strengthened by the inconsistent results obtained with the ‘abortus’ and ‘melitensis’ suspensions of FBAT, as illustrated by our work and recently published work from Tanzania [50]. Long and repeated experience [11,18,24,51] shows that the most plausible reasons for these inconsistencies are deficient standardisation of antigen suspensions and poor antigen quality.…”
Section: Discussionmentioning
confidence: 72%
“…In our study, out of the 38 patients presenting with UTI, only 9 (24%) had confirmed SBI. A low (18%) [19] and high (30%) [22] proportion of SBI in UTI in febrile children have been reported. UTI remains the most common cause of nonlocalized fever in children below 2 years of age and can be a co-infection in confirmed viral infections as well [21].…”
Section: Discussionmentioning
confidence: 99%
“…The proportion of SBI is known to vary between 24 to 40%, according to geographical area and the age of children [18,19]. We choose a proportion of 30% from above studies to calculate the sample size.…”
Section: Sample Size Calculationmentioning
confidence: 99%
“…Other studies evaluating causes of febrile illness in African children have focused on a limited number of pathogens [30][31][32][33]. In a study of febrile children in Tanzania utilizing serologic, culture, and molecular assays, viruses accounted for 51% of lower respiratory infections, 78% of systemic infections, and 100% of upper respiratory infections [34].…”
Section: Discussionmentioning
confidence: 99%